Borders And Beyond - - (Yayasan Pustaka Obor Indonesia, 2018)
This book contributes to a better understanding about the dynamics of transnational migration and diaspora in Northern Thailand border areas with Myanmar and Laos. Border cities in Southeast Asia are places that have unique characteristics because of rapid development which includes the process of transnational migration and diaspora communities from neighboring countries. Historically, different ethnic groups had migrated in the border areas of mainland Southeast Asian countries and China. Border cities, such as Mae Sai and Chiang Khong, are strategic places for refugees, minority groups, and others from neighboring countries to reside either temporary or permanently.